MUTU PENDIDIKAN SEBAGAI STRATEGI PEMASARAN JASA PENDIDIKAN STUDI KASUS PADA SD PANGUDI LUHUR BERNARDUS SEMARANG: Penelitian Kualitatif - Susanto, Andrias Eko; Eko Pramono, Suwito; Widiyanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Education as an important pillar in the progress of a nation is entering a period of increasingly open interaction between entities around the world. The world of education competes to maintain its existence by prioritizing the attractiveness and excellence of each. Schools as quality educational institutions are able to carry out the educational process in accordance with established quality standards or criteria. Quality standards that include inputs, processes and products must be aligned. The research used is descriptive qualitative method. To maintain existence, schools need to market educational services to the community. Parent satisfaction is a very effective strategy in marketing increasingly competitive educational services in Semarang City. SD Pangudi Luhur Bernardus Semarang sees that the marketing strategy through quality can be realized with 7P efforts; product, price, location, place, promotion, people, physical evidence, and process. SD Pangudi Luhur Bernardus Semarang is a quality school because it has excellent human resources, sufficient financing, and adequate facilities. This is one of the advantages possessed by SD Pangudi Luhur Bernardus Semarang as a quality educational institution that is able to answer the needs of the community which has an impact on the PPDB process